Building an HPSG-based Indonesian resource grammar (INDRA) - Moeljadi, David (2016)
This paper presents the creation and the initial stage development of a broad-coverage Indonesian Resource Grammar (INDRA) within the framework of Head Driven Phrase Structure Grammar (HPSG) (Pollard and Sag, 1994) and Minimal Re-cursion Semantics (MRS) (Copestake et al., 2005). At the present stage, INDRA focuses on verbal constructions and sub-categorization since they are fundamental for argument and event structure. Verbs in INDRA were semi-automatically acquired from the English Resource Grammar (ERG) (Flickinger, 2000) via Wordnet Bahasa (Nurril Hirfana Mohamed Noor et al., 2011; Bond et al., 2014). In the future, INDRA will be used in the development process of machine translation. A preliminary evaluation of INDRA on the MRS test-suite shows promising coverage.